Vitamin D Prevalence among Older Adults Hospitalized in a French Geriatric Hospital - Lopez-Leret, Diana; Schlatter, Joël (Archives of Clinical and Biomedical Research, 2024)
Background: Vitamin D deficiency is associated with harmful impacts on various organism functions. This is particularly the case for the elderly who have higher risk of developing a vitamin D deficiency because of low sunlight exposure, inadequate nutrition, and age-related physiological changes. The aim of this study was to determine the prevalence of vitamin D deficiency in older inpatients. Methods: Retrospective study was conducted at a French geriatric hospital among adults (>65 years) having a vitamin D serum dosage. A total of 149 participants were included in the study. The demographic data (age and sex), body mass index (BMI), presence of fracture, medication of antiepileptic and glucocorticoid, calcium and phosphorus blood values, serum albumin value, and vitamin D treatment initiation were performed during the study period. Results: The study population was between 65 to 100 years old with a mean vitamin D level of 18.7 ± 11.8 μg/L. In total, 29.5% patients demonstrated severe vitamin D deficiency (<12.0 μg/L) and 59% patients demonstrated vitamin D deficiency (12-30 μg/L). Statistical significant correlation was found between the calcium and vitamin D level (Pearson coefficient=0.2669, p=0.006982) and gender and vitamin D level (Mann-Whitney test, p=0.04). Hypocalcaemia (<2.2 mmol/L) was found in 11.4%. For many patients (76%), vitamin D supplementation was initiated according to the local protocol (100,000 IU of cholecalciferol every 15 days for 2 months). For any patient, vitamin D blood control was performed. Conclusions: Prevalence of vitamin D deficiency among older adults is considerably high often associated with reduced calcium levels. The current results suggest that vitamin D supplementation would be started in this risk group associated with a blood examination at the end of treatment to ensure its effectiveness.